RAINFALL PREDICTION USING CNN - Deepa K, Kokila M, Nandhini A, Pavethra A, Umadevi M (International Journal of Advanced Science and Technology, 2020)
A tale precipitation expectation strategy has been proposed. A two-advance technique has been utilized. Greedy forward determination calculation is utilized to diminish the list of capabilities and to locate the most encouraging highlights for precipitation forecast. In the first place, in the preparation stage the information is prepared by framework, Neural Network (NN) is applied. The proposed two stage forecast model one is utilizing AI approach and another is Neural system approach has been applied. The information for trial intention is gathered online over the period from 1901 to 2015. The exploratory outcomes have proposed a sensible improvement over customary techniques in anticipating precipitation. The proposed beat the looked at models by accomplishing 84.26% precision.